Manajemen Strategis di Bawah Kerangka Kerja ESG: Meningkatkan Keberlanjutan Perusahaan dan Kepercayaan Pemangku Kepentingan - Wira Natali Angeline Lumban Gaol; Soeratin, Harry Z; Miftah, Munasiron (Accounting Student Research Journal, 2024)
In an era where business sustainability is becoming increasingly important, Strategic Management Under an ESG Framework has become a key focus for many companies. With the increasing awareness of environmental, social, and corporate governance issues, companies around the world are increasingly realizing that their long-term success is not only determined by their financial performance, but also by their impact on the environment and society. In this context, the research aims to explore how the application of ESG principles in strategic management can improve corporate sustainability and strengthen stakeholder trust. The research uses a qualitative method through an analytical descriptive approach, where the theory or basis of discussion is taken from the results of literature studies such as books, articles and relevant journals, by also describing the theories, findings, and other research materials obtained from reference materials as the basis for research activities. This aims to understand the importance of ESG integration for strategic decision making so as to identify new opportunities to create long-term value, reduce risks, and build better relationships with stakeholders.